2021
DOI: 10.3389/fcell.2021.650106
|View full text |Cite
|
Sign up to set email alerts
|

Complex Crystal Structure Determination and in vitro Anti–non–small Cell Lung Cancer Activity of Hsp90N Inhibitor SNX-2112

Abstract: SNX-2112, as a promising anticancer lead compound targeting heat shock protein 90 (Hsp90), absence of complex crystal structure of Hsp90N-SNX-2112 hindered further structural optimization and understanding on molecular interaction mechanism. Herein, a high-resolution complex crystal structure of Hsp90N-SNX-2112 was successfully determined by X-ray diffraction, resolution limit, 2.14 Å, PDB ID 6LTK, and their molecular interaction was analyzed in detail, which suggested that SNX-2112 was well accommodated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…As illustrated in Figure 4, Hsp90 showed a melting point of 47.68 ± 0.46°C, while the complex of C4 and hsp90 was 28.47 ± 0.48°C. The marked changes of Δ T m (−18.85 ± 0.56°C) demonstrated that C4 exhibited high affinity with Hsp90, even better than SNX‐2112 (−9.51 ± 1.00°C) (D. Zhao et al, 2021), 22g (10.92 ± 0.60°C) (Xu et al, 2020) and comparable with radicicol (21.32 ± 0.29°C). However, the Δ T m caused by matrine was only 0.04 ± 0.39°C.…”
Section: Resultsmentioning
confidence: 98%
“…As illustrated in Figure 4, Hsp90 showed a melting point of 47.68 ± 0.46°C, while the complex of C4 and hsp90 was 28.47 ± 0.48°C. The marked changes of Δ T m (−18.85 ± 0.56°C) demonstrated that C4 exhibited high affinity with Hsp90, even better than SNX‐2112 (−9.51 ± 1.00°C) (D. Zhao et al, 2021), 22g (10.92 ± 0.60°C) (Xu et al, 2020) and comparable with radicicol (21.32 ± 0.29°C). However, the Δ T m caused by matrine was only 0.04 ± 0.39°C.…”
Section: Resultsmentioning
confidence: 98%
“…In the early stage, our group successfully determined the complex crystal structures of the target Hsp90 N and its four small molecule inhibitors. [3,4,16,17] In this study, computer-aided molecular docking technology was applied to predict the complex 3D structures of the target Hsp90 N and its four inhibitors. Moreover, the comparison between the simulated 3D structures and crystal structures was thoroughly analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…[11] The discovery of Hsp90 inhibitors has been an important strategy for new anticancer drug development. [12][13][14][15] Previously, the crystal structures of four small molecule inhibitors (Debio0932, SNX-2112, KW-2478, and NVP-AUY922) and Hsp90 N have been successfully determined by our group, [3,4,16,17] which would promote structural optimization of inhibitors and deepen the understanding of molecular mechanisms behind Hsp90. Herein, Sybyl software was applied to build the simulated 3D structure of the four abovementioned inhibitors and Hsp90 N by molecular docking.…”
Section: Introductionmentioning
confidence: 99%